A Syntactic Analysis on Efl's Writing Text on Writing Task 2 IELTS - Sudarmono (JLER (Journal of Language Education Research), 2025)
This study analyzes syntactic structures in EFL students' writing on IELTS Writing Task 2 using qualitative methods. Through in-depth analysis of the texts, the study aims to identify patterns and syntactic errors that frequently appear and how these affect the quality of arguments in the writing. A qualitative research method, which aims to deeply analyze the syntactic structures in EFL (English as a Foreign Language) students' writing on IELTS Writing Task 2. This method was chosen because it allows researchers to explore in detail and depth the elements of language used by writers, especially in terms of sentence structure and grammatical structure. The analysis revealed a general pattern in the use of sentence structure that can affect the coherence and cogency of students' arguments, with some recurring syntactic errors found. Comparison with previous studies revealed that there are certain trends in the development of EFL students' syntactical skills in their writing. This study concludes that a better understanding of syntactic structures is essential for EFL students to improve the quality of their writing in academic contexts. The findings are expected to provide insights for teachers and curriculum developers in designing more effective learning strategies to improve students' writing skills.